Effects of substrate and fertilization on growth of Cymbidium sp. from tissue cultured at nursery stage - Nguyen , Thị Nguyệt; To , Thị Thùy Trinh; Nguyen, Thị Sáu; Le , Thị Hồng Ngọc; Nguyen , Thị Huệ; Vuong , Thị Hồng Loan (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The study was performed at Center for Business Incubation of Agricultural High Technology, Cu Chi District, Ho Chi Minh City from January to December 2023. The objective was formulated substrate and fertilizer suitable for the growth of tissue cultured Cymbidium orchids at the nursery stage. Research includes, the content one had seven substrate formulas and the content two had nine fertilizer formulas. Each experiment was designed single-factor randomized complete design (CRD), 3 replications. The result showed that the mix substrate of 50% coco peat + 25% tree fern fiber + 25% rice husk or 50% coco peat + 25% rice husk + 25% peanut shell and Growmore 30-10-10 (2 times) + Seaweed (1 time) and Vitamin B1 (1 time) are suitable for the growth of Cymbidium sp. at the nursery stage. Five months after planting, the Cybiudium orchid plant height (22.8 cm), number of leaves/plant (12.6 leaves), number of pseudobulbs/plant (2.2 pseudobulbs) were significantly different compared to the control and the remaining fertilizer formulas.